Unravelling the Intricacies: An In-depth Analysis of the Complexity within South African Local Government - Nkoana, Isaac; Mmachoene, Modiba; Selelo, Mohale Ernest (Publica: Jurnal Pemikiran Administrasi Negara, 2024)
The aim of this paper is to investigate the how complexity affects local government in South Africa. Local government is the closest sphere to the local people in South Africa. This sphere of government is charged with the responsibility of providing goods and services to the public. However, local governments in South Africa are glued to complexity that produce ineffectiveness and inefficiency in terms of providing goods and services to the local communities. This paper relies on an assertion by Prof. Nghamula Nkuna, who refers complexity within local government as a situation where people or stakeholders do not confine themselves to a single site, nor do they always engage others in the same manner. He further states that the manner in which the ward public officials of a local municipality chair the ward committee meeting is different from the way he or she reports to the local traditional leader, and interactions vary as obligations and roles shift depending on the situation. For example, most councillors elected to local government are also employed as teachers, and they are also serving in other community structures. The findings indicate that the complexity within local government create multiple challenges, such as ineffective decision-making, slow implementation of policies, policy fragmentation and inconsistency, and strained relationships and collaboration. The paper is purely qualitative, which adopts literature-based methodology. It concludes that local government, where most public officials hold one position, do well in terms of delivering services because there is no conflict of interest. This paper recommends that local government should enforce a single-site duty towards public officials so that they engage others in the same manner to circumvent challenges created by the complexity within local government.